2017
DOI: 10.3390/rs9020119
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Rice Agriculture across Myanmar Using Time Series Sentinel-1 Assisted by Landsat-8 and PALSAR-2

Abstract: Assessment and monitoring of rice agriculture over large areas has been limited by cloud cover, optical sensor spatial and temporal resolutions, and lack of systematic or open access radar. Dense time series of open access Sentinel-1 C-band data at moderate spatial resolution offers new opportunities for monitoring agriculture. This is especially pertinent in South and Southeast Asia where rice is critical to food security and mostly grown during the rainy seasons when high cloud cover is present. In this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
157
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(173 citation statements)
references
References 54 publications
(70 reference statements)
1
157
0
Order By: Relevance
“…These data have already been tested in rice and land-cover monitoring [38,39,43]. However, specific applications of these data in mapping subsistence or smallholder commercial rice agriculture typical in urban landscapes are yet to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data have already been tested in rice and land-cover monitoring [38,39,43]. However, specific applications of these data in mapping subsistence or smallholder commercial rice agriculture typical in urban landscapes are yet to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Land-cover classification accuracies have been improved with the conjugative use of optical and microwave datasets [39,43]. In the current study, it is proposed that the integration of the aforementioned optical indices with temporal microwave data could provide additional information that would improve overall classification accuracy.…”
Section: Image Classificationmentioning
confidence: 99%
“…Underlying the proximate causes of mangrove loss are drivers unique to Myanmar. Rice expansion is smallholder-driven to enhance livelihoods and employment (Okamoto 2007, Matsuda 2009, Stokke et al 2018; interventions dating back to the 1980s include capital intensification, development of irrigation infrastructure, agricultural mechanisation, crop diversification, and improvement of agricultural management practices; and market liberalisation and reforms in 2003 further incentivised rice expansion (Okamoto 2007, Matsuda 2009, Torbick et al 2017. Mangrove conversion to oil palm in Myanmar (Richards and Friess 2015), in contrast, was driven by large-scale agribusiness concessions, particularly targeting Tanintharyi (Connette et al 2016), to meet domestic and industrial demands for palm oil and achieve self-sufficiency in edible oils (Donald et al 2015).…”
Section: Underlying Drivers Of Mangrove Cover Changementioning
confidence: 99%
“…Another similar study monitoring rice fields revealed that here the temporal backscatter change was higher. Torbick et al (Torbick et al, 2017) also used the radar backscatter coefficient of the S1 series to monitor rice crops in order to map the rice growing areas of Myanmar, in South-Eastern Asia, their cropping calendar, flooding and crop intensification. Pathier et al also showed the high importance of high spatial resolution of the Sentinel-1 series.…”
Section: Contribution Of Sentinel-1 Satellite Images To Vegetation Momentioning
confidence: 99%